The Supraorbital Eyebrow Craniotomy for Intra- and Extra-Axial Brain Tumors: A Single-Center Series and Technique Modification. Issue 6 (3rd August 2020) - Ansari, Shaheryar F; Eisenberg, Amy; Rodriguez, Amanda; Barkhoudarian, Garni; Kelly, Daniel F
Abstract: BACKGROUND: The supraorbital (SO) eyebrow craniotomy provides minimally invasive access to the anterior and middle fossae and parasellar region. OBJECTIVE: To present a series of patients treated with the SO approach to assess outcomes, the impact of endoscopy, and describe a modified pericranial flap aimed at reducing postoperative frontalis paresis and hypesthesia. METHODS: A retrospective analysis was undertaken of our prospective database of patients who underwent SO craniotomy for tumor/cyst removal. Patients were evaluated based on pathology, utility of endoscopy, extent of resection, complications, and functional/esthetic recovery. RESULTS: From 2007 to 2018, 129 operations were performed in 117 patients (54% women; mean age 60 ± 16.5 yr). The most common lesions were meningiomas (43%), gliomas (15%), and metastases (15%). Prior surgery and/or radiation had been performed in 37% and 26% of patients, respectively. Endoscopy was used in 76 (61%) operations and allowed more complete tumor removal in 38 (50%). For first-time operations, gross-total removal was achieved in 78%. Major complications included stroke (3%), cranial nerve deficit (3%), acute hematoma (1%), and cerebrospinal fluid leak (1%). The modified pericranial flap technique used in 18 recent patients resulted in a shorter duration of transient frontalis paresis and forehead hypesthesia with complete functional recovery in all 18. CONCLUSION: The SO craniotomy is an effective keyhole approach for intra- and extra-axial tumors. Endoscopic assistance may allow additional tumor removal in almost 30% of the cases. The modified pericranial flap appears to accelerate functional recovery, although additional patients and follow-up are required to better assess this technique.